2014
DOI: 10.1007/s11606-013-2690-z
|View full text |Cite
|
Sign up to set email alerts
|

“We’ve Not Gotten Even Close to What We Want to Do”: a Qualitative Study of Early Patient-Centered Medical Home Implementation

Abstract: BACKGROUND:The Veterans Health Administration (VA) Patient Aligned Care Team (PACT) initiative is designed to deliver a medical home model of care associated with better patient outcomes, but success will depend in part on the model's acceptability and sustainability among clinic employees. OBJECTIVE: We sought to identify key themes in the experience of primary care providers, nurse care managers, clerical and clinical associates, and clinic administrators implementing PACT, with the aim of informing recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 22 publications
6
27
0
Order By: Relevance
“…Participants felt their dedication to keeping veterans at home and their accountability to their veterans exceeded what exists in traditional, in‐person clinical care in models such as PACT in the VA. The interdisciplinary nature of the teams led to development of close‐knit, longitudinal relationships with the veterans, whereas primary care clinical environments like PACT have experienced challenges with staffing, team development, and training . Past VA research has also shown that reduced continuity of PCPs decreased odds of excellent communication with patients .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants felt their dedication to keeping veterans at home and their accountability to their veterans exceeded what exists in traditional, in‐person clinical care in models such as PACT in the VA. The interdisciplinary nature of the teams led to development of close‐knit, longitudinal relationships with the veterans, whereas primary care clinical environments like PACT have experienced challenges with staffing, team development, and training . Past VA research has also shown that reduced continuity of PCPs decreased odds of excellent communication with patients .…”
Section: Discussionmentioning
confidence: 99%
“…The interdisciplinary nature of the teams led to development of close-knit, longitudinal relationships with the veterans, whereas primary care clinical environments like PACT have experienced challenges with staffing, team development, and training. 27 Past VA research has also shown that reduced continuity of PCPs decreased odds of excellent communication with patients. 28 Thus, the strong continuity of care HBPC provides, combined with effective communication, seems to be a significant factor contributing to high-quality care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] Prior studies have indicated that lack of understanding of roles within PCMH models is an important source of confusion and dissatisfaction among PCPs and staff. [15][16][17] Yet the degree to which staff and PCPs agree regarding allocation or sharing of specific primary care tasks is not known.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Effective care coordination, however, requires appropriate resources. 16 In the VA, inadequate staffing and time constraints are well-documented challenges of PACT implementation, [17][18][19][20] often associated with higher staff burnout 18 and lower scores on PACT implementation metrics. 19 Competing care delivery priorities and lack of communication from leadership about PACT performance metrics are additional challenges.…”
Section: Introductionmentioning
confidence: 99%